Spirografh Media for Kindergarten Teachers of ‘Aisyiyah in Tanjung Sari Village - Deliati Deliati; Ratna Sari Dewi; Gusman Lesmana (BIRCU, 2019)
This Community Activities Program is in the form of training for kindergarten teachers in Tanjung Sari Village, Medan Selayang, North Sumatra Province. The aim to be achieved in this activity is to increase the creativity of kindergarten teachers using spirografh media to improve fluency and train the fingers of kindergarten children in writing exercises, because the fingers of nerve movements that are accustomed to children will be happy and happy in learning and training the eyes to focus on what he does, the benefits of training children to be diligent and patient in doing assignments in class. This PKM activity is carried out collaboratively with partner schools through several approach methods such as participatory approaches, group approaches, individual approaches, lecture methods, and discussion methods. The training activity begins with socializing to ABA kindergarten teachers, the basic concept of spirografh media. Furthermore, understanding the concept is manifested in the form of giving exercises on variations in spirografh media pattern gear that will form a beautiful and interesting work. The results of community service activities for partner schools are in the form of increasing knowledge / insights and experiences of teachers - kindergarten teachers related to the concepts and practices of spirografh media which can then be implemented in each class in each kindergarten. so that it provides a significant contribution to improve children's writing exercises in carrying out learning activities.